„Perspektywy gwiazdarskie”. Lunety w literaturze i piśmiennictwie naukowym polskiego baroku - Raubo, Grzegorz (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The telescope played a crucial role in the modern scientific revolution and occupied a significant place in Baroque culture. Interest in the telescope has been confirmed by Polish literary sources and writings, including scientific treatises and compendia of knowledge. Telescopes are the subject of works on the popularization of science written in the scientia curiosa convention. Reflections on the telescope appear in the context of deliberations on the world system, on the possibility of the existence of life forms on the Moon and other celestial bodies, and in the context of polemic against Aristotelian cosmology. The telescope is an element of religious deliberations concerning eschatology and those focused on astronomy, whose aspiration to get to know the universe is motivated by secular curiosity. The matter of conducting observations of the sky with the use of the telescope has turned into a comedy show, in a satirical way relating to the practice of astrology.